"Atd" angle index as a method for estabilishing localization of the carpal triradius on the palm - Marcinkiewicz, Stanisław; Marcinkiewicz, Danuta; Pietruska, Oktawia (Anthropological Review, 1977)
In the paper the authors describe their own new method for estabilishing localization of carpal triradius on the surface of the palm. Material constituting the base for the present study consists of palm prints and hand outlines of 574 individuals of both sexes in age of 4 to 20 years. The authors have found significant differences between children and adults in values of atd angle (tab. 1) and length-breadth index of hand (tab. 2). It follows that value of atd angle is related to length-breadth index of hand. Both these characters undergo changes during development. Hence the authors propose to describe localization of carpal triradius with use of the atd Angle Index that is computed as follows: $$\frac{\text{atd angle (in radians)}} {\text{(length-breadth index of hand)}} {· 100}$$ There are no siginificant differences between atd Angle Index of children and of adults (tab. 3).